KONSEP ISLAMIC LEADERSHIP SULTAN MUHAMMAD AL-FATIH - Moch Mahsun; Ilfi Nur Diana (STAI ALHIKMAH Jakarta, 2022)
AbstractThis article aims to provide a clear picture of the concept of Islamic Leadership of Sultan Muhammad al-Fatih. With the descriptive analysis method, it is known that he practices spirituality as an Islamic Based Development actor which is a picture of a leader who can influence others to do something useful to the organization and oneself. This research describes the leadership of an Islamic figure who upholds Islamic principles. This research is also expected to add scientific insight around Islamic leadership as an optional to be applied today and in the future.AbstrakArtikel ini bertujuan untuk memberikan gambaran yang jelas tentang konsep Islamic Leadership Sultan Muhammad al-Fatih. Dengan metode analisis deskriptif diketahui bahwa beliau mempraktik spiritualitas sebagai aktor Islamic Based Development yang merupakan gambaran pemimpin yang dapat mempengaruhi kepada orang lain untuk melakukan sesuatu bermanfaat terhadap organisasi dan diri sendiri. Pelitian ini mendiskripsikan gambaran kepeminpinan dari seorang tokoh Islam yang menjunjung tinggi prinsip-prinsip Islam. Penelitian ini juga diharap menambah wawasan keilmuan seputar leadership Islam sebagai opsional untuk diaplikasikan masa ini dan di masa mendatang.